Twenty thousand leagues under the sea. - Verne, Jules 1828-1905. (New York Dodd, Mead, 1952)
A nineteenth-century science fiction tale of an electric submarine, its eccentric captain, and undersea world, which anticipated many of the scientific achievements of the twentieth century.
Keywords: Underwater exploration -- Fiction; Submarines (Ships) -- Fiction; Submarines -- Fiction; Science fiction; Sea stories; Science fiction....